A Suggested Model for Quantitative Assessment of Plantations with Particular Reference to Pakela Teak Plantations of South Bastar Division (M.P.) - Suri, S. K. (Indian Forester, 1984)
The urgent need for assessing the growth performance of plantations, standardizing the methodology, drawing up an Assessment Manual and undertaking the task of assessment in an organised manner throughout the country has been discussed, emphasised and a model has been suggested.Quantitative assessment of Pakela Teak Plantations of S. Bastar Division bas been done and tbe methodology of the model adopted bas been described. The concept of Growth Achievement Index (G.A.I) has been developed and discussed Tbe criterion for rating the plantation has been given. It has been concluded from tbls study that the slle quality of Pakela teak plantations is All India Q. II.